Atomic-like charge qubit in a carbon nanotube enabling electric and magnetic field nano-sensing - I. Khivrich (Nature Portfolio, 2020)
Among the recent developments in quantum technologies, the use of qubits for quantum sensing has led to significant improvements in resolution and sensitivity at the nanoscale. Here, the authors present a carbon nanotube charge qubit that can act as a highly sensitive scanning probe of electric and magnetic fields.